2007
DOI: 10.1002/cncr.23136
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of mesenteric tumor nodules in patients with stage III colorectal cancer

Abstract: BACKGROUND. Tumor nodules are occasionally found in adjacent mesentery of colorectal cancer specimens and are felt to reflect a worse prognosis. The clinical significance of mesenteric tumor nodules was investigated. METHODS. A review of 786 patients with stage III colorectal cancer referred between 1995 and 1999 was undertaken. TNM staging was standardized by considering mesenteric nodules separately and not assigning them to T or N categories. Survival analyses were performed. RESULTS. Mesenteric tumor nodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 6 publications
3
29
0
Order By: Relevance
“…164 Because of their heterogenous nature, these lesions have often been mixed with other types of venous 163,165,168,169 or lymphatic invasion, 163,169 lymph node metastasis, 163 nerve infiltration, 163,165,166,168e170 or otherwise nonspecified infiltration of the peri-visceral fat, 165,168,169 thus making it difficult to compare data from different studies and explaining differences in the hazard ratios between the different works. 164 Studies that considered as TDs all those metastatic occurrences not associated with lymph node involvement showed that these lesions, when grouped as a whole, have a prognosis similar to that of stage III disease, 168,171 thereby failing to provide evidence to Figure 15 Macroscopic view of the mesorectum. The protuberances indicated by the arrows correspond to the lateral lymph nodes that should be kept separated from the lymph nodes found within the mesorectum.…”
Section: Lymphatic and Venous Invasionmentioning
confidence: 99%
“…164 Because of their heterogenous nature, these lesions have often been mixed with other types of venous 163,165,168,169 or lymphatic invasion, 163,169 lymph node metastasis, 163 nerve infiltration, 163,165,166,168e170 or otherwise nonspecified infiltration of the peri-visceral fat, 165,168,169 thus making it difficult to compare data from different studies and explaining differences in the hazard ratios between the different works. 164 Studies that considered as TDs all those metastatic occurrences not associated with lymph node involvement showed that these lesions, when grouped as a whole, have a prognosis similar to that of stage III disease, 168,171 thereby failing to provide evidence to Figure 15 Macroscopic view of the mesorectum. The protuberances indicated by the arrows correspond to the lateral lymph nodes that should be kept separated from the lymph nodes found within the mesorectum.…”
Section: Lymphatic and Venous Invasionmentioning
confidence: 99%
“…Studies that considered as tumor deposits all those metastatic occurrences not associated with lymph node involvement showed that these lesions, when grouped as a whole, have a prognosis similar to that of stage III disease, 14,15 thereby failing to provide an evidence basis to substantiate its inclusion in the TNM system. 16 Results of a recent meta-analysis based on survival involving 3714 patients, although confirming the consistent adverse prognostic value of tumor deposits, illustrated differences in the hazard ratios between the different studies.…”
mentioning
confidence: 99%
“…Satellite tumour deposits are considered the equivalent of nodal metastases (a lymph node replaced by tumour), even if they lack residual nodal architecture, and are staged as N1c disease in the absence of other nodal metastases, thus upstaging our patient's disease from N0 to N1c. The presence of these mesenteric tumour deposits is a strong adverse prognostic feature 7 8…”
Section: Discussionmentioning
confidence: 99%